A test case for physical mapping of human genome by repetitive sequence fingerprints: construction of a physical map of a 420 kb YAC subcloned into cosmids. - Bellanné-Chantelot, C (1991)
A rapid and safe method of Yeast Artificial Chromosome (YAC) physical mapping by cosmid 'fingerprinting' is presented. YACs are subcloned into cosmids which are prepared without previous separation of cloned DNA from host DNA. Groups of overlapping clones are detected according to their restriction fragments size and intensity after hybridization with total human DNA. To test this approach, a cosmid library was constructed from total DNA of a yeast strain containing a 420 kb YAC. A single contig of 84 clones was obtained with a minimal detectable overlap of 60% i.e. a 9.2 fold representative library. Large scale physical mapping of YACs would take full advantage of the DNA preparation procedure employed in this work and allows to take into account restriction fragment intensities.